“Linking Religiosity and Experience” A Study of Muslim-Friendly Tourism Intentions: Integration of Tourism Consumption Systems Theory and Social Exchange Theory - Ibrahim, Muhammad Hanif; Khairi, Lukluk Ilmatul; Putri, Akmalia Lutfiaturrosyida Agung (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2025)
This study investigates the primary determinants of Muslim-friendly tourism intentions, emphasizing the roles of Islamic attributes, destination image, past behavior, and attitudes. It further analyzes how religiosity moderates these relationships to uncover the factors shaping Muslim travelers’ tourism intentions. 300 Muslim participants from various regions were surveyed, and the data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). This research uniquely applies the Tourism Consumption System Theory (TCS) and Social Exchange Theory (SET) to understand Muslim tourists’ decision-making processes. By integrating these theoretical lenses, the study presents a holistic perspective on Muslim travel behavior’s cultural, psychological, and economic drivers. The results demonstrate that Islamic attributes, a strong destination image, and prior positive travel experiences significantly influence Muslim-friendly tourism intentions. Moreover, favorable attitudes toward tourism also enhance these intentions. Religiosity is a significant moderating factor, intensifying the influence of Islamic attributes and destination image on tourism intentions. These findings provide important implications for tourism industry practitioners seeking to attract Muslim tourists. Marketing strategies and destination branding that reflect Islamic attributes can increase attractiveness while acknowledging religiosity’s role, allowing for more tailored and meaningful experiences. The results serve as a valuable resource for policymakers and tourism operators to design inclusive and sustainable tourism programs that specifically address the needs of Muslim travelers, thereby supporting economic development and fostering intercultural understanding.